To what extent can differences in energy prices and digitalization explain why Europe has fallen behind the United States in economic growth in the 21st century? - Söderpalm,Axel (2025)
This thesis explores a central question in the macroeconomic debate today: Why has Europe`s economic growth lagged behind the United States in recent decades? The study specifically examines if this divergence in part can be explained by differences in digitalization and energy prices. By employing an OLS panel data model with country specific effects – modelling the two samples of EU15 countries and EU15 plus the United States – this study aims to estimate the relationship between the two macroeconomic variables and real GDP growth in the 2000s so far. The goal is to contribute to the contemporary growth debate in macroeconomics. The results show a significant negative effect from energy prices on growth in both samples, while the proxy of digitalization showed a relatively weak effect in the two. When including the US, the results did not change in a fundamental way. This means that no conclusions on the variables’ possible role in recent growth dynamics can be drawn. However, this study contributes to the ongoing debate on why there is a growth divergence between the US and Europe – focusing on specific structural factors.
Keywords: Economic growth; Digitalization; Energy Prices; Panel data analysis; Europe-US comparison